SUPPRESSION OF THE 1876 NATIONAL STATEHOOD RESTORATION EFFORTS IN FERGANA BY THE TURKESTAN MILITARY DISTRICT - Makhmudov Komal Samadovıch (Journals Park Publishing, 2022)
Although the Kokand Khanate was liquidated in Fergana Valley and the Polatkhan uprising was suppressed, the actions of national austerity against the colonization of the Empire would not stop. The uezd (district) and precinct officials within the Fargona region, which have just been established, have great difficulties in maintaining public order in places and eliminating the rising folk movements. Therefore, the colonial authorities in the Fergana region carried out their activities, relying on the forces of the Turkestan Military District.
Keywords: sports dentistry, prevention of injuries and diseases of the dental system of contact sports.